1984
DOI: 10.1055/s-2007-969679
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Investigations onRhaponticum carthamoides

Abstract: The central neurotropic activity of an aqueous-alcoholic extract from Rhaponticum carthamoides (Wilid.) (Leucea carthamoides D.C.) cultivated in Bulgaria was studied in experiments on albino mice, rats and cats. In doses up to 40 g/kg the extract was non-toxic. Administered in definite doses in mice and rats, it exerted a moderate central stimulating action: increased ambulation and rearing in rats ("open field" test); increased central nervous system excitability ("jumping" test); had a slight antinarcotic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…8 Hz and the doublet signal of arabinose anomeric proton H-1Љ had a chemical shift 4.29 ppm with coupling constant 8. 4 Hz. HMBC correlations from H-1Ј to C-9 confirmed the attachment of glucose unit to aglycon, and the position of arabinose unit was confirmed by correlations from H-1Љ to C-6Ј and from H-6Ј b to C-1Љ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Hz and the doublet signal of arabinose anomeric proton H-1Љ had a chemical shift 4.29 ppm with coupling constant 8. 4 Hz. HMBC correlations from H-1Ј to C-9 confirmed the attachment of glucose unit to aglycon, and the position of arabinose unit was confirmed by correlations from H-1Љ to C-6Ј and from H-6Ј b to C-1Љ.…”
Section: Resultsmentioning
confidence: 99%
“…Collision induced dissociation experiments were performed from 10 mM ammonium acetate solution, colliding [MϩNa] ϩ and [MϩNH 4 ] ϩ ions in positive ion mode and [MϪH] Ϫ ion in negative ion mode with argon gas. The proton-proton coupling constants were obtained from the 1 H spectrum and phase-sensitive COSY spectra and refined with PERCH spectral analysis software.…”
Section: Resultsmentioning
confidence: 99%
“…According to the IR spectra, higher concentrations of organic acids are found in the methanol + H 2 O fraction (E). These acids were also extracted into fraction D. 20 Table 3. This fraction contained low amounts of cadmium, zinc and lead (1.1-4.7% of total content).…”
Section: Resultsmentioning
confidence: 99%
“…DC, the Siberian medicinal plant. 19,20 Various important therapeutic compounds (phytoecdysteroids, flavonoids, stilbene, sesquiterpene lactones (guaianolides), polyacetylenes and N-feruloylserotonin isomers) are contained in different parts of this plant. Their role in plant stress metabolism is not fully explained.…”
Section: Speciation Analysis and Environmentmentioning
confidence: 99%
“…Research has shown that this herb has a number of bioactive effects such as antimicrobial [3,4], anti-cancer [5 -8], antidepressant, anti-inflammatory, and antidiabetic effects [9 -11]. It has also been reported to enhance liver regeneration and memory [12,13]. It has been defined as an adaptogen because of its ability to increase the resistance of an organism to environmental stress factors and avoid damage from such factors [14 -16].…”
Section: Introductionmentioning
confidence: 99%